Affordable Housing For Low-Income Masses: A Case Study of A Densely Populated Area in Lagos Metropolis - Ajayi, Oluranti Olupolola; Faremi, Olajide Julius; Roger, Simeon Dele; Uwaje, Antony (CSID Journal of Infrastructure Development, 2020)
A house is an essential facility that affords an abode, provides habitation and shelter adequacies. Affordable housing presumes access to a conducive, functional, and sustainable dwelling by the majority of the people within a locality. The study investigated the factors mitigating the actualization of affordable housing for low-income masses in the selected area. Survey research was adopted for the study. The population for the study is made up of two groups comprising low-income masses and construction professionals. The study adopted a multi-sampling method. Both convenient and random sampling techniques were utilized to gather information from the respondents. Statistical Package for Social Sciences (SPSS) was used for descriptive (frequency, percent, and mean score) and appropriate inferential analysis. Results indicated factors weighing down the provision of affordable housing as well as factors precluding accessible housing for low-income masses. Also, the response from construction professionals showed the level of agreement on factors impeding the provision of affordable housing. The trail to alleviate the effect of the non-affordability of housing for low-income masses becomes perceptible and addressed.